Evaluation of a disease risk index for adult patients undergoing umbilical cord blood transplantation for haematological malignancies. (19th October 2017) - Paviglianiti, Annalisa; Ruggeri, Annalisa; Volt, Fernanda; Sanz, Guillermo; Milpied, Noel; Furst, Sabine; Esquirol, Albert; Arcese, William; Picardi, Alessandra; Ferra, Christelle; Ifrah, Norbert; Bourhis, Jean H.; et al.
Summary: A disease risk index (DRI) has been defined for stratifying heterogeneous cohorts of patients undergoing allogeneic haematopoietic stem cell transplantation (HSCT). This index defines 4 distinct groups with different outcomes, dividing patients by disease type and status and considering cytogenetics for acute myeloid leukaemia and myelodysplastic syndromes (MDS). Recently, the DRI has been refined to include rare diseases and improve MDS stratification by blast percentage and response to prior therapy. Previous reports on DRI include only a small number of UCBT recipients. The current study aims to determine the applicability of the DRI for patients undergoing unrelated cord blood transplantation (UCBT). We retrospectively analysed 2530 adults receiving UCBT between 2004 and 2014. Diagnosis was acute leukaemia (AL) in 66% of the cases. Overall survival (OS) at 2 years was 56 ± 3% for patients with low DRI ( n = 352), 46 ± 1% for intermediate DRI ( n = 1403), 28 ± 2% for high ( n = 489) and 20 ± 4% for very high DRI ( n = 109) ( P < 0·001). In the multivariate model, DRI remained an independent risk factor for OS. Similar findings were observed for PFS and DRI. Our results show the applicability of DRI for stratifying UCBT recipients and confirm the prognostic value of this simple and robust tool in this setting.